Current Scenario of Environmental Pollution & Its Solution by Plantation In Changing Climate - Kabir, Muhammad; Habiba, Um e; Rehman Farooqi, Zia-Ur (Universitas Diponegoro, 2021)
Life’s quality is depending on quality of environment. As environment creates favorable surroundings for survival, growth and development of existing organisms. All living organisms are affected indirectly or directly due to environmental pollution. It is due to rapid increases in human being. Environmental pollution especially by anthropogenic activities is a main problem facing the world today and there is a need for increasing attentiveness that a clean and green environment is essential for better growth of living organisms in this changing climate of World. It is our top most priority to keep our country clean and green as cleanness is a part of our faith. Thus environmental pollution is causing great threat to plants, animals and to human all over the world. As each and every problem has a solution, because problem is always artificial, man desires to find the solution. In recent innovations there is a need to develop clean and green spaces within and around the polluted areas for existence of better environment. As some plants can act as pollution sink working as natural lungs. So,“the green revolution (Plantation) is the best solution to arrest the pollution”. If haphazard population growth goes on increasing without realizing the importance of trees especially those which act as pollution sink then there would be more critical changes for living organisms in near coming future